2020
DOI: 10.1371/journal.pone.0232064
|View full text |Cite
|
Sign up to set email alerts
|

Impact of knee marker misplacement on gait kinematics of children with cerebral palsy using the Conventional Gait Model—A sensitivity study

Abstract: Clinical gait analysis is widely used in clinical routine to assess the function of patients with motor disorders. The proper assessment of the patient's function relies greatly on the repeatability between the measurements. Marker misplacement has been reported as the largest source of variability between measurements and its impact on kinematics is not fully understood. Thus, the purpose of this study was: 1) to evaluate the impact of the misplacement of the lateral femoral epicondyle marker on lower limb ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 31 publications
2
16
0
Order By: Relevance
“…Regarding displacements of individual markers, displacements of the thigh and tibia wands and the knee marker in the anterior-posterior axis had the largest calculated impact on kinematics, all with an RMSD angle of over 5° in the transversal plane (Figure 4). These ndings con rmed previous results demonstrating the knee marker's high impact in the anterior-posterior axis in the transversal plane but it's very low impact when displaced in the proximal-distal axis 12,13 . Even though some studies have reported improvements in calibration methods, such as the Knee Alignment Device, marker placement reproducibility and reliability remains the CGM's most signi cant limitation 17 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Regarding displacements of individual markers, displacements of the thigh and tibia wands and the knee marker in the anterior-posterior axis had the largest calculated impact on kinematics, all with an RMSD angle of over 5° in the transversal plane (Figure 4). These ndings con rmed previous results demonstrating the knee marker's high impact in the anterior-posterior axis in the transversal plane but it's very low impact when displaced in the proximal-distal axis 12,13 . Even though some studies have reported improvements in calibration methods, such as the Knee Alignment Device, marker placement reproducibility and reliability remains the CGM's most signi cant limitation 17 .…”
Section: Discussionsupporting
confidence: 90%
“…The present sensitivity analysis used a procedure similar to that of a previous study 13 . All subjects were equipped with the CGM marker set 3 (14 mm) and walked barefoot at a self-selected speed along a 10 m walkway.…”
Section: Testing Proceduresmentioning
confidence: 99%
“…Misplacement (e.g., due to different protocols / practices among physicians, obesity, subject's morphology / wounds / cooperation spirit) may account for an angle error exceeding the 5 o acceptance limit which is what a trained eye is likely to differentiate [1]. The study of 10 children with cerebral palsy against 10 agedmatched typical developing children, showed that anterior-posterior misplacement of the lateral epicondyle marker, led to hip internal-external rotation angle offsets of 5.3 o per 10mm of displacement [7]. Determination of the ankle's internal-external rotation angle, demonstrated a sensitivity of 4.4 o per 10mm offset.…”
Section: Related Workmentioning
confidence: 99%
“…Naturally, measurements tend to worsen according to the ratio of the misplacement to leg length: the smaller the length, the bigger the angle error. It was concluded that in order to achieve an error below the limit of 5 o on all joints, a physician needs a repeatability precision below 1.2% of the leg length when placing the markers [7].…”
Section: Related Workmentioning
confidence: 99%
“…Reproducibility studies have been performed in the literature to evaluate different sources of variability in gait analysis (McGinley et al 2009 ; Wren et al 2011 ). Some studies have performed a sensitivity analysis on joint axes for a given type of joint motion (Della Croce et al 1999 ; Fonseca et al 2020 ). More specifically, knee joint kinematics is known to be prone to non-linear error propagation, which results in the well-known kinematic effect of cross-talk (Baudet et al 2014 ; Pothrat et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%